Enzimatic Processing of Lignocellulosic Biomass for Pulp Making: A Review - Fitria, Fitria (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Pulp (cellulose fiber suspension) is the main raw material in paper and medium density fiber (MDF) board industry. The critical process in pulping is to break down the linkage of cell wall component among lignin, hemicellulose and cellulose in order to get individual fiber of cellulose. To enhance fiber refining, pretreatment method can be applied on biomass before pulping either chemical, mechanical, thermal, biological or combination of the processes. Biological process can be chosen due to its ability to degrade the lignin so that the cellulose fiber can be taken easier. This process, called biopulping uses a set of enzymes produced by white rot fungi. This paper reviews broad improvement of biopulping and its impact to the environmental friendly goal.Keywords: pulp, biopulping, natural fiber, white-rot fungi, lignocellulosic biomass